Contaminación acústica y su influencia sobre la salud de los pobladores de las zonas de las calles abelardo quiñones y participación del distrito de San Juan Bautista - Vasquez Dacosta, Andy (2022)
The work was developed in the Avenue Abelardo Quiñones and Avenue the Participation, county of Maynas, Saint John the Baptist District, the objective was to determine if the acoustic contamination influences on the satisfaction of people that you/they live in this avenues, the evaluations they were carried out in schedules of tomorrow, late and night respectively, the work is explanatory of type correlational, the design is explanatory, with quantitative and qualitative data, the population was conformed by the self-driven park that you/they traffic for the avenues in study conformed by cars, trucks, lineal motos, motorcars, etc., to determine the statistical significance of the levels of acoustic contamination for sampling point the technique of the variance analysis it was used and to determine the interaction of the levels of contamination with the degree of the resident's satisfaction the test chi-square it was used (x2), being obtained the following results: that, in the av. Abelardo Quiñones, the acoustic contaminations in the evaluation points are statistically same, but the averages are superior to the permissible standards, being the point of evaluation of the hills the one that showed the average of more absolute value; in the av. participation the acoustic contaminations in the evaluated shifts are statistically differing, where the tomorrow's averages is superior to the permissible standards and statistically superior to the averages of the other shifts, where it stands out the average of 68.88 decibels for the tomorrow's shift.